2015
DOI: 10.1007/s10508-015-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

When Parsimony Is Not Enough: Considering Dual Processes and Dual Levels of Influence in Sexual Decision Making

Abstract: The literature on sexual decision making that has been used to understand behaviors relevant to HIV and STI risk has relied primarily on cognitive antecedents of behavior. In contrast, several prominent models of decision making outside of the sexual behavior literature rely on dual process models, in which both affective and cognitive processing are considered important precursors to behavior. Moreover, much of the literature on sexual behavior utilizes individual-level traits and characteristics to predict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
0
5
0
3
Order By: Relevance
“…One implication of our findings is that, in order to maximize ecological validity, future lab-based research on sexual response and decision-making (e.g., the effects of arousal on behavior) should be conducted at times of day or in states of tiredness that more closely match the real-world conditions in which sexual decisions are commonly being made. Our findings also highlight the need for studies utilizing intensive longitudinal assessment, such as daily diaries, to gather details on time of day when sexual activity begins and on levels of concomitant tiredness, antecedent sleep quality, and co-occurring substance use, in order to better capture person-by-situation interactions regarding sex (Cooper, 2010; Rendina, 2015). Finally, research could also explore indirect pathways from tiredness to sexual behavior via intervening factors such as impaired emotion regulation or increased negative affect.…”
Section: Discussionmentioning
confidence: 96%
“…One implication of our findings is that, in order to maximize ecological validity, future lab-based research on sexual response and decision-making (e.g., the effects of arousal on behavior) should be conducted at times of day or in states of tiredness that more closely match the real-world conditions in which sexual decisions are commonly being made. Our findings also highlight the need for studies utilizing intensive longitudinal assessment, such as daily diaries, to gather details on time of day when sexual activity begins and on levels of concomitant tiredness, antecedent sleep quality, and co-occurring substance use, in order to better capture person-by-situation interactions regarding sex (Cooper, 2010; Rendina, 2015). Finally, research could also explore indirect pathways from tiredness to sexual behavior via intervening factors such as impaired emotion regulation or increased negative affect.…”
Section: Discussionmentioning
confidence: 96%
“…B. Lust, Versagensangst, aber auch Lust am Risiko, eine wichtige Rolle; Emotionen beeinflus-sen das Verhalten maßgeblicher als Kognitionen (Rendina 2015). So braucht es also beides: kognitives Wissen über Risiken, aber auch die Fähigkeit, darauf in einer sexuellen Situation zuzugreifen.…”
Section: Diskussionunclassified
“…Given that a large proportion of the variability in sexual decision making occurs within individuals (i.e., intra individual) over a series of events (i.e., sexual episodes), rather than between individuals (i.e., inter individual) [14], it has been suggested that models of sexual decision making should take into account both trait-like factors as well as within-person situational state-like factors [15]. Between-person differences on a number of globally measured, trait-like factors—such as intentions or motivations for condom use [9], self-efficacy [7], sensation seeking [16], sexual compulsivity [17], and negative emotionality (e.g., depression) [18]—have been associated with global measures of sexual risk.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when experiencing sexual arousal, college-aged males were more likely to make riskier sexual decisions [51]. Rendina [15] has argued that the heightened affect and physiological arousal leading up to, and during, sexual activity influence decision making, particularly to the extent that such affective and physiological states can bias cost–benefit considerations that underlie decision making. We propose that this biasing effect of sexual arousal on sexual decision making is more potent or influential among those with high IGT scores, given that higher IGT scores generally reflect a greater degree of noticing one’s internal bodily or affectively influenced “thermostat” and adaptively adjusting subsequent cognitive and health decision making.…”
Section: Introductionmentioning
confidence: 99%